Endoplasmic reticulum stress in disease pathogenesis - Lin, Jonathan H; Walter, Peter; Yen, T S Benedict (Annual review of pathology, 2008)
The endoplasmic reticulum (ER) is the site of synthesis and folding of membrane and secretory proteins, which, collectively, represent a large fraction of the total protein output of a mammalian cell. Therefore, the protein flux through the ER must be carefully monitored for abnormalities, including the buildup of misfolded proteins. Mammalian cells have evolved an intricate set of signaling pathways from the ER to the cytosol and nucleus, to allow the cell to respond to the presence of misfolded proteins within the ER. These pathways, known collectively as the unfolded protein response, are important for normal cellular homeostasis and organismal development and may also play key roles in the pathogenesis of many diseases. This review provides background information on the unfolded protein response and discusses a selection of diseases whose pathogenesis involves ER stress.